Reference electrode for three-electrode lithium ion battery, preparation method of reference electrode and lithium ion battery

By adopting a composite protective layer structure on the lithium metal reference electrode, lithium metal components are used to improve their stability, and the problem of lithium metal reference electrodes can be easily oxidized and corroded. Battery performance.

CN119361600AActive Publication Date: 2025-01-24XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411494657.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

In existing three-electrode lithium-ion batteries, lithium metal reference electrodes are susceptible to oxidation and corrosion in the air, which affects the accuracy of the test results. Their placement inside the battery will hinder the transmission of lithium ions and affect the performance of the battery.

Method used

The composite protective layer structure includes a polymer solid electrolytic film formed by polytic ethylene and first lithium salt as the first protective layer, and a metal organic frame material and a membrane polymer with a metal solution with lithium salt ionic liquid solution The formation of li-IL@MOFS/polymer composite membrane is used as the second protection layer, and lithium metal parts are packed to improve their stability.

Benefits of technology

Through the packaging of the composite protective layer, the contact between lithium metal components and air is reduced, its stability is improved, and the contact and side effects of the electrolyte are avoided. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361600A_ABST
    Figure CN119361600A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, particularly relates to a lithium metal reference electrode for a three-electrode lithium ion battery, and further relates to a preparation method of the lithium metal reference electrode and the three-electrode lithium ion battery comprising the lithium metal reference electrode. The lithium metal reference electrode comprises a polymer solid electrolyte membrane serving as a first protective layer and a lithium metal part which is used as a second protective layer and is encapsulated by a Li-IL (at) MOFs / polymer composite membrane based on a metal organic framework material, so that when the whole reference electrode is arranged on the outer side of a battery cell, the lithium metal part can be used as a lithium metal reference electrode; the risk of corrosion of the lithium metal reference electrode during use is reduced, and the stability of the lithium metal reference electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and specifically relates to a lithium metal reference electrode for a three-electrode lithium ion battery. The present invention also relates to a method for preparing the lithium metal reference electrode and a three-electrode lithium ion battery comprising the lithium metal reference electrode. Background Art

[0002] As global warming and air pollution become increasingly prominent, green and low-carbon development and energy conservation and emission reduction have become the mainstream of the times. At the same time, as an effective means of energy conservation and carbon reduction, new energy vehicles play an important role in the green and low-carbon circular economy system, thus bringing broad development space for pure electric vehicles powered by lithium-ion batteries. The slow lithium embedding process of graphite negative electrodes of lithium-ion batteries limits the further development of fast charging technology applications. Evaluating the lithium embedding capacity of graphite negative electrodes and reducing the risk of lithium deposition during fast charging have become a key research task in the application of fast charging technology.

[0003] At the beginning of the 21st century, in order to compensate for the measurement errors caused by various factors such as electrolyte, electrode materials and current path in the two-electrode system, some people have begun to try to introduce a reference electrode that is stable in the electrolyte and has a known potential to construct a three-electrode system, so as to achieve independent measurement and precise potential control of the working electrode (analyzed object). In short, the three-electrode system is to construct a current test circuit between the working electrode and the counter electrode, and a voltage test circuit between the working electrode and the reference electrode, forming a classic "three-electrode two-circuit" system. Based on the characteristic that the reference electrode can provide a stable potential reference, the potential of the working electrode can be independently measured. Introducing it into the lithium-ion battery system can analyze the electrochemical behavior of the negative electrode material of the lithium-ion battery during the charging and discharging process, especially the potential change of the negative electrode during the fast charging process. It provides more reliable data support for the detection of the lithium plating boundary current (maximum charging current) and lithium plating behavior of the negative electrode. Therefore, the three-electrode system has also become a commonly used electrochemical method in the research of fast charging technology.

[0004] Chinese invention patent CN 114284564 B discloses a method for preparing a soft-pack battery having a constant potential reference electrode by placing a lithium metal sheet on the outside of the battery cell. By using a lithium metal sheet as a reference electrode, in order to eliminate the oxide layer on the surface of the lithium metal, the oxide layer is electrochemically treated by constant current discharge to obtain a reference electrode with a constant potential, and the analysis of lithium potential and impedance changes of the positive and negative electrodes under different states is realized. Although this method takes into account the oxidation of the lithium metal sheet, the production cycle of the battery cell is relatively long, which will further increase the degree of oxidation of the lithium metal. Although electrochemical treatment is carried out in the later stage, a dissolution reaction occurs and the oxide layer is gradually peeled off, but it is inevitable that excessive oxygen elements will be introduced into the entire sealed battery system and the electrolyte, which increases the adverse effects on the battery system, and thus affects the battery capacity.

[0005] Chinese invention patent application CN 117007658 A discloses a method for making a solid electrolyte coated reference electrode. The insulating layer is removed by partially treating a metal wire containing an insulating layer and lithium foil is wrapped on the treated area to form a lithium layer, and then a solid electrolyte is coated on the outside of the metal lithium layer, or a solid electrolyte is coated on the metal wire and then lithium is plated to form a lithium layer. The solid electrolyte reduces the probability of metal parts falling off, and at the same time isolates the reference electrode from direct contact with the positive and negative electrodes, slows down the side reaction between the reference electrode and the electrolyte, and ensures the stability of the reference electrode. However, since the reference electrode containing a solid electrolyte layer is placed between the positive and negative electrodes inside the battery, the reference electrode and the outermost solid electrolyte layer will affect the transmission of lithium ions during the charge and discharge test, especially causing uneven lithium insertion in the negative electrode portion blocked by the reference electrode, affecting the accuracy of the experimental test results. Therefore, further optimization is needed for the entire three-electrode test structure.

[0006] In summary, choosing lithium metal as the reference electrode does not require long-term lithium plating compared to electrochemical lithium plating, and the choice of placement is more flexible. Electrochemical lithium plating must be placed between the positive and negative electrodes containing lithium sources inside the battery cell, otherwise it will be difficult to achieve lithium plating, but this will also have an adverse effect of hindering lithium ion transmission. Lithium metal can effectively avoid this unfavorable factor.

[0007] Since lithium metal is a highly active alkali metal, when exposed to air, its surface will be immediately corroded by oxygen and water in the air, causing various uncontrollable adverse reactions and producing various heterogeneous pollutants, which will affect the accuracy of the test results when used as a three-electrode reference electrode. Therefore, the isolation protection of lithium metal when used as a reference electrode is particularly important, and it is necessary to use appropriate technology to build an air / water stable protective layer on its surface to reduce its reactivity with ambient air. Summary of the invention

[0008] Purpose of the Invention

[0009] In view of the problems existing in the prior art described in the above background technology section, the purpose of the present invention is to provide a lithium metal reference electrode for a three-electrode lithium-ion battery. The present invention also relates to a method for preparing the lithium metal reference electrode and a three-electrode lithium-ion battery comprising the lithium metal reference electrode.

[0010] Technical Solution

[0011] In order to achieve the above object, the present invention adopts the following technical solutions:

[0012] Scheme 1: A lithium metal reference electrode for a three-electrode lithium-ion battery, comprising a lithium metal component, a wire, a first protective layer and a second protective layer, wherein

[0013] The lithium metal component comprises a lithium element content of about ≥ 98.0 wt %, preferably about ≥ 99.0 wt %, and more preferably about ≥ 99.9 wt %;

[0014] The second protective layer comprises a Li-IL@MOFs / polymer composite film formed by a metal-organic framework material (Metal-Organic Frameworks, abbreviated as MOFs) adsorbed with a second lithium salt ionic liquid (Ionic Liquid, abbreviated as IL) solution and a film-forming polymer, and the film encapsulates the lithium metal component;

[0015] The first protective layer comprises a polymer solid electrolyte membrane formed of polyvinylidene fluoride (PVDF) and a first lithium salt, the membrane encapsulating the lithium metal component and the second protective layer; and

[0016] One end of the wire is electrically connected to the lithium metal component, and the other end of the wire extends out of the second protective layer and the first protective layer encapsulating the lithium metal component.

[0017] Option 2: The lithium metal reference electrode according to Option 1 above, wherein the lithium metal component is selected from lithium foil, lithium sheet, lithium plate or lithium mesh.

[0018] Option 3: The lithium metal reference electrode according to Option 1 or 2 above, wherein the lithium metal component has a thickness in the range of about 0.1 to about 1 mm.

[0019] Option 4: The lithium metal reference electrode according to any one of Options 1 to 3 above, wherein the conductive wire comprises a copper wire.

[0020] Option 5: The lithium metal reference electrode according to any one of options 1 to 4 above, wherein the thickness of the first protective layer is in the range of about 0.1 to about 0.5 mm.

[0021] Option 6: The lithium metal reference electrode according to any one of options 1 to 5 above, wherein the thickness of the second protective layer is in the range of about 0.5 mm to about 1 mm.

[0022] Option 7: A lithium metal reference electrode according to any one of Options 1 to 6 above, wherein the first lithium salt and the second lithium salt each independently contain one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide) and lithium bis(trifluoromethylsulfonylimide).

[0023] Option 8: A lithium metal reference electrode according to any one of Options 1 to 7 above, wherein the first lithium salt and the second lithium salt are the same and are selected from one of lithium hexafluorophosphate, lithium bis(difluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.

[0024] Option 9: A lithium metal reference electrode according to any one of Option 1 to Option 8 above, wherein the molecular weight of the polyvinylidene fluoride is in the range of about 300,000 to about 1,100,000 Daltons.

[0025] Option 10: A lithium metal reference electrode according to any one of the above options 1 to 9, wherein the mass ratio of the polyvinylidene fluoride to the first lithium salt is in the range of about (2.9-3.1):1.

[0026] Scheme 11: A lithium metal reference electrode according to any one of Schemes 1 to 10 above, wherein the ionic liquid comprises one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide.

[0027] Option 12: A lithium metal reference electrode according to any one of options 1 to 11 above, wherein the film-forming polymer comprises polyvinyl alcohol (PVA) having a molecular weight in the range of about 120,000 to about 150,000 Daltons.

[0028] Scheme 13: A lithium metal reference electrode according to any one of Schemes 1 to 12 above, wherein the metal organic framework material is prepared from zinc nitrate and dimethylimidazole in methanol.

[0029] Scheme 14: A lithium metal reference electrode according to any one of schemes 1 to 13 above, wherein during the formation of the Li-IL@MOFs / polymer composite film of the second protective layer, the molar concentration of the second lithium salt ionic liquid solution used is in the range of about 1 to about 3 mol / L.

[0030] Scheme 15: A lithium metal reference electrode according to any one of schemes 1 to 14 above, wherein during the formation of the Li-IL@MOFs / polymer composite film of the second protective layer, the mass ratio of the metal organic framework material to the second lithium salt ionic liquid solution is in the range of about (1.4-1.6):1.

[0031] Scheme 16: A lithium metal reference electrode according to any one of schemes 1 to 15 above, wherein during the formation of the Li-IL@MOFs / polymer composite film of the second protective layer, the mass ratio of the metal organic framework material adsorbed with the second lithium salt ionic liquid solution to the film-forming polymer is in the range of about (2-2.5):1.

[0032] Scheme 17: A method for preparing a lithium metal reference electrode according to any one of Schemes 1 to 16 above, wherein the method comprises the following steps:

[0033] Step 1: providing the lithium metal component electrically connected to one end of the wire;

[0034] Step 2: providing a Li-IL@MOFs / polymer composite membrane as the second protective layer, comprising dissolving the second lithium salt in the ionic liquid to obtain the second lithium salt ionic liquid solution, mixing the second lithium salt ionic liquid solution with the metal organic framework material, so that the second lithium salt ionic liquid solution is adsorbed in the metal organic framework material, and then uniformly mixing and grinding the metal organic framework material adsorbed with the second lithium salt ionic liquid solution and the film-forming polymer, and hot-pressing the obtained ground mixture into a film to form the Li-IL@MOFs / polymer composite membrane, wherein the size of the Li-IL@MOFs / polymer composite membrane is sufficient to encapsulate the lithium metal component;

[0035] Step 3: providing a polymer solid electrolyte membrane as the first protective layer, comprising dissolving the polyvinylidene fluoride and the first lithium salt in a volatile organic solvent to form a solution, and volatilizing the organic solvent in the solution to form the polymer solid electrolyte membrane, wherein the size of the polymer solid electrolyte membrane is sufficient to encapsulate the lithium metal component encapsulated by the Li-IL@MOFs / polymer composite membrane;

[0036] Step 4: The lithium metal component obtained in step 1 is encapsulated in sequence with the Li-IL@MOFs / polymer composite membrane obtained in step 2 and the polymer solid electrolyte membrane obtained in step 3 to form the lithium metal reference electrode, which comprises the polymer solid electrolyte membrane, the Li-IL@MOFs / polymer composite membrane and the lithium metal component in order from the outside to the inside, wherein the other end of the wire electrically connected to the lithium metal component extends out of the polymer solid electrolyte membrane and the Li-IL@MOFs / polymer composite membrane encapsulating the lithium metal component.

[0037] Scheme 18: A preparation method according to Scheme 17 above, wherein step 4 comprises: stacking the Li-IL@MOFs / polymer composite membrane obtained from step 2 and the lithium metal component obtained from step 1 on the polymer solid electrolyte membrane obtained from step 3 in the order of "Li-IL@MOFs / polymer composite membrane", "lithium metal component" and "Li-IL@MOFs / polymer composite membrane", and then further providing a polymer solid electrolyte membrane as the first protective layer on the uppermost Li-IL@MOFs / polymer composite membrane to form a combination, and then fusing and compounding the polymer solid electrolyte membrane and the Li-IL@MOFs / polymer located in the encapsulation area in the obtained combination to complete the encapsulation.

[0038] Scheme 19: A preparation method according to Scheme 17 above, wherein step 4 comprises: stacking the polymer solid electrolyte membrane obtained from step 3, the Li-IL@MOFs / polymer composite membrane obtained from step 2, and the lithium metal component obtained from step 1 in the order of "polymer solid electrolyte membrane", "Li-IL@MOFs / polymer composite membrane", "lithium metal component", "Li-IL@MOFs / polymer composite membrane" and "polymer solid electrolyte membrane" to form a combination, and then fusing and compounding the polymer solid electrolyte membrane and the Li-IL@MOFs / polymer located in the encapsulation area of ​​the obtained combination to complete the encapsulation.

[0039] Scheme 20: The preparation method according to Scheme 18 or 19 above, wherein the fusion compounding comprises hot pressing at a temperature of about 40 to about 70° C. and a pressure of about 5 to about 10 MPa for about 15 to about 30 seconds.

[0040] Scheme 21: A preparation method according to any one of Schemes 17 to 20 above, wherein the adsorption process in the step 2 comprises maintaining the mixture comprising the second lithium salt ionic liquid solution and the metal organic framework material at a temperature of about 100 to about 120°C and a vacuum degree of about -0.06 MPa to about -0.08 MPa for about 12 to about 24 hours to allow the second lithium salt ionic liquid solution to be adsorbed in the metal organic framework material.

[0041] Scheme 22: The preparation method according to any one of Schemes 17 to 21 above, wherein the hot pressing film forming in step 2 comprises maintaining the film at a temperature of about 70 to about 80° C. and a pressure of about 18 to about 30 MPa for about 2 to about 5 minutes.

[0042] Scheme 23: A preparation method according to any one of Schemes 17 to 22 above, wherein the volatile organic solvent used in step 3 comprises one or more of acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.

[0043] Scheme 24: A preparation method according to any one of schemes 17 to 23 above, wherein the formation of the polymer solid electrolyte membrane in step 3 includes forming the membrane at a temperature of about 40 to about 60°C and at a vacuum degree of about -0.04 to about -0.08 MPa.

[0044] Scheme 25: A preparation method according to any one of Schemes 17 to 24 above, wherein the solid content of the solution formed in step 3 is controlled within a range of about 5 to about 10 weight %.

[0045] Scheme 26: A three-electrode lithium-ion battery comprising a battery cell, wherein the battery cell comprises a separator, a negative electrode and a positive electrode, wherein the three-electrode lithium-ion battery further comprises a lithium metal reference electrode according to any one of the above schemes 1 to 16 or a lithium metal reference electrode prepared according to the preparation method according to any one of claims 17 to 25.

[0046] Option 27: A three-electrode lithium-ion battery according to Option 26 above, wherein the lithium metal reference electrode is preferably placed outside the battery cell and closer to the negative electrode relative to the positive electrode.

[0047] Option 28: A three-electrode lithium-ion battery according to Option 26 or 27 above, wherein the size of the lithium metal reference electrode is smaller than the size of the negative electrode.

[0048] Technical Effects

[0049] The present invention realizes the protection of the lithium metal components in the lithium metal reference electrode through a composite protective layer. Specifically, the present invention realizes the encapsulation and protection of the lithium metal components by using a double-layer structure formed by a solid electrolyte membrane based on polyvinylidene fluoride (PVDF) (as a first protective layer) and a metal organic framework material (Li-IL@MOFs material) / polymer composite membrane adsorbed with a lithium salt ionic liquid solution (as a second protective layer). The composite protective layer of the present invention reduces the possibility of the lithium metal components contacting with the air, improves the stability of the lithium metal components in the air, and thus improves the stability of the lithium metal reference electrode.

[0050] In addition, the lithium metal reference electrode of the present invention can be located as a whole outside the battery cell of the three-electrode lithium-ion battery, thereby reducing the impact of the introduction of the reference electrode on the entire battery cell system.

[0051] The composite protective layer constructed by the present invention solves some problems caused by preparing a three-electrode system based on lithium metal as a reference electrode, and specifically has the following outstanding advantages:

[0052] (1) From the perspective of the three-electrode system architecture, compared with the prior art solution of placing a metal current collector such as copper wire between the positive and negative electrodes in the common battery cell and then plating lithium by electrochemical deposition, in the design of the present invention, lithium metal is placed between the battery cell and the aluminum-plastic film, so that the battery can be tested after it is offline, without the need for long-term forward and reverse lithium plating, which is more convenient and quick to use;

[0053] (2) From the perspective of material properties, polyvinyl alcohol (PVA) as a film-forming polymer is almost unaffected by weak acids, weak bases or organic solvents and has a certain chemical stability. At the same time, PVA is easy to form a film and has good mechanical strength and processing properties. PVA can play a cross-linking role and can effectively improve the brittle fracture defects of single Li-IL@MOFs materials during the process of pressing into films, and can effectively enhance the flexibility of Li-IL@MOFs / polymer composite films;

[0054] (3) Metal-organic framework materials (MOFs) have the advantages of high specific surface area, high porosity, adjustable pore size and the ability to accommodate a large number of gas or liquid molecules. The abundant pore space can form an ion migration path after the lithium salt is adsorbed, ensuring that the reference electrode and the working electrode can be ion-conductive, forming an effective test circuit. At the same time, the MOFs microporous structure has a high surface energy and strong adsorption capacity, and can have a certain adsorption capacity for air, water, etc. to protect the lithium metal interface and reduce the oxidation risk of lithium metal.

[0055] (4) Since polyvinylidene fluoride (PVDF) is chemically stable to water and air, the double-layer membrane composed of the solid electrolyte membrane based on PVDF and the Li-IL@MOFs / polymer composite membrane can construct an air / water stable protective layer on the surface of lithium metal through synergistic action, reduce its reactivity with ambient air, and reduce the risk of corrosion by water and oxygen in the air, thereby achieving multiple protections for lithium metal;

[0056] (5) The encapsulation of the composite protective layer of the present invention can avoid the contact between lithium metal and electrolyte, reduce the occurrence of side reactions between lithium metal and electrolyte, thereby improving the stability of the lithium metal reference electrode in the corrosive electrolyte and ensuring the accuracy of the lithium reference electrode potential monitoring;

[0057] (6) From the perspective of processing and preparation, the use of hot / mechanical pressing to form a membrane reduces the use of organic solvents in the membrane formation process compared to wet casting. It does not require the dissolution and dispersion process of the polymer and MOFs mixed material in the organic solvent, which shortens the membrane preparation time. At the same time, the use of organic solvents can easily lead to incomplete solvent evaporation and adsorption of organic solvents in the pores of MOFs, higher solvent removal temperatures, and difficulty in removal.

[0058] (7) Lithium metal components such as lithium sheets, lithium meshes, and lithium foils have a higher lithium content than the lithium layer formed by electrochemical lithium plating. Reference electrodes based on lithium metal components will also have longer static and dynamic lifespans. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] In order to more clearly illustrate the technical solutions of the specific implementation methods of the present invention, the drawings required for use in the specific implementation methods will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0060] Figure 1 An exploded view schematically illustrating the components of the lithium metal reference electrode of the present invention;

[0061] Figure 2 is a stereoscopic view of the assembled lithium metal reference electrode of the present invention;

[0062] Figure 3 is a top view of the assembled lithium metal reference electrode of the present invention;

[0063] Figure 4 An exploded view schematically illustrating the components of a three-electrode lithium-ion battery of the present invention;

[0064] Figure 5 is an assembly diagram of the three-electrode lithium-ion battery of the present invention after assembly;

[0065] Figure 6 is a step charge and discharge curve diagram of the three-electrode lithium-ion battery of Example 3 of the present invention; and

[0066] Figure 7 This is a graph showing the reference electrode-negative electrode potential stability test of the three-electrode lithium-ion battery of Example 3 of the present invention.

[0067] Reference numerals:

[0068] 1: First protective layer; 2: Second protective layer; 3: Lithium metal component; 4: Wire; 5: Diaphragm; 6: Negative electrode; 7: Positive electrode; 8: Positive electrode tab; 9: Negative electrode tab; 10: Tab glue; 11: Reference electrode tab; 12: Reference electrode DETAILED DESCRIPTION

[0069] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without paying creative work belong to the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on normal conditions.

[0070] In the description of the present invention, the terms "upper", "lower", "front", "back", "left", "right", "inside", "outside" and the like indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and do not require that the present invention must be constructed and operated in a specific direction. Therefore, they should not be understood as limitations on the present invention. The terms "connected", "connected" and "set" used in the present invention should be understood in a broad sense. For example, they can be fixed connections or detachable connections; they can be directly connected or indirectly connected through intermediate components; they can be wired electrical connections, radio connections, or wireless communication signal connections. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0071] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. The term "about" used in the present invention means that the modified numeral can fluctuate within the range of ±20%, ±15%, ±10%, ±5% or ±2% of the numeral. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in the present invention.

[0072] According to a first aspect of the present invention, the present invention provides a lithium metal reference electrode for a three-electrode lithium ion battery, the lithium metal reference electrode comprising a lithium metal component, a wire, a first protective layer and a second protective layer. The various components included in the lithium metal reference electrode will be described in detail below.

[0073] Lithium Metal Components:

[0074] In the lithium metal reference electrode of the first aspect of the present invention described above, the lithium metal component contains a lithium element content of at least about 98.0% by weight, preferably at least about 99.0% by weight, and more preferably at least about 99.9% by weight.

[0075] The shape of the lithium metal component is not particularly limited, but in a preferred embodiment of the present invention, the lithium metal component can be formed into any one of lithium foil, lithium sheet, lithium plate and lithium mesh. Here, the thickness of the lithium foil, lithium sheet, lithium plate and lithium mesh is not particularly limited, but in a preferred embodiment of the present invention, the thickness can be set in the range of about 0.1 to about 1 mm commonly used in the art, for example, about 0.2 mm, about 0.3 mm, about 0.4 mm, about 0.5 mm, about 0.6 mm, about 0.7 mm, about 0.8 mm or about 0.9 mm.

[0076] First and second protective layers:

[0077] In the lithium metal reference electrode of the first aspect of the present invention, the second protective layer comprises a Li-IL@MOFs / polymer composite film formed by a metal organic framework material adsorbed with a second lithium salt ionic liquid solution and a film-forming polymer, which encapsulates the lithium metal component.

[0078] In the lithium metal reference electrode of the first aspect of the present invention, the first protective layer comprises a polymer solid electrolyte membrane formed of polyvinylidene fluoride and a first lithium salt, which encloses the lithium metal component and the second protective layer.

[0079] The lithium salt used in the first protective layer and the second protective layer:

[0080] In the lithium metal reference electrode of the first aspect of the present invention, the first lithium salt in the first protective layer and the second lithium salt in the second protective layer may be the same or different. However, since the reference electrode and the protective layer are in the same electrolyte system of the entire battery cell, different types of lithium salts dissolved in the electrolyte may affect the battery cell system, and may participate in the reaction and produce various by-products during the charge and discharge process, thereby affecting the battery cell test. Therefore, in a preferred embodiment, the first lithium salt and the second lithium salt are the same.

[0081] Here, the first lithium salt and the second lithium salt may each independently include one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide) and lithium bis(trifluoromethylsulfonylimide). Particularly preferably, the first lithium salt and the second lithium salt are the same and are selected from any one of lithium hexafluorophosphate, lithium bis(difluorosulfonylimide) and lithium bis(trifluoromethylsulfonylimide).

[0082] Ionic liquid used in the second protective layer:

[0083] In the lithium metal reference electrode of the first aspect of the present invention, the ionic liquid used in the process of forming the second protective layer is an organic ionic liquid. For example, in a preferred embodiment, the ionic liquid used may include one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt and 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt.

[0084] Film-forming polymer used in the second protective layer:

[0085] In the lithium metal reference electrode of the first aspect of the present invention, the film-forming polymer used in the process of forming the second protective layer preferably includes polyvinyl alcohol. From the perspective of material properties, polyvinyl alcohol as a film-forming polymer is almost unaffected by weak acids, weak bases or organic solvents, and has a certain chemical stability. At the same time, polyvinyl alcohol is easy to form a film, has good mechanical strength and processing properties, can play a cross-linking role and can effectively improve the brittle fracture defects of a single Li-IL@MOFs material during the pressing process of the film, and can effectively enhance the flexibility of the Li-IL@MOFs / polymer composite film.

[0086] Here, it is particularly preferred to use polyvinyl alcohol having a molecular weight in the range of about 120,000 to about 150,000 Daltons, for example, about 130,000 Daltons or about 140,000 Daltons. The molecular weight of the polyvinyl alcohol should not be too large, for example, should not exceed about 150,000 Daltons, otherwise, during the film forming process, the uniformity of the film layer is difficult to control; nor should it be too small, for example, should not be less than about 120,000 Daltons, otherwise, the mechanical properties of the formed film may be poor, for example, the formed film may be soft, thereby increasing the difficulty of demolding.

[0087] Process parameters for forming the second protective layer:

[0088] In a preferred embodiment, during the formation of the second protective layer, the concentration of the second lithium salt solution in the IL is about 1 to about 3 mol / L, for example, about 1.5 mol / L, about 2 mol / L or about 2.5 mol / L. Here, the concentration of the solution should not be too high, for example, it should not exceed about 3 mol / L, otherwise the lithium salt may not be completely dissolved; nor should it be too low, for example, it should not be less than about 1 mol / L, otherwise it may affect the formation of the lithium ion conductive network and affect the ion transport kinetics.

[0089] In a further preferred embodiment, during the formation of the second protective layer, the mass ratio of the MOFs material to the IL solution of the second lithium salt is controlled within a range of about (1.4-1.6): 1, for example, about 1.5: 1. Here, the mass ratio range should not be too large, for example, it should not exceed about 1.6: 1, otherwise after the MOFs completely adsorb the Li-IL solution, the unadsorbed pores of the MOFs may adsorb too much electrolyte; it should not be too small, for example, it should not be less than about 1.4: 1, otherwise it may cause incomplete adsorption of the Li-IL solution by the MOFs, and excessive Li-IL solution, so that the prepared sample is in a clumping and wet state, which is not conducive to subsequent experimental preparation and sampling.

[0090] In another further preferred embodiment, in the process of forming the second protective layer, the mass ratio of the metal organic framework material (Li-IL@MOFs) adsorbed with the second lithium salt ionic liquid solution to the film-forming polymer is controlled within the range of about (2.0-2.5):1, for example, about 2.1:1, about 2.2:1, about 2.3:1 or about 2.4:1. Here, the mass ratio range should not be too large, for example, it should not exceed about 2.5:1, otherwise it may cause the cross-linking effect of the film-forming polymer to be unclear, and the flexibility after film formation is poor, resulting in the formed film being easily brittle; it should not be too small, for example, it should not be less than about 2.0:1, otherwise it may cause the mechanical properties of the formed film to deteriorate and the uniformity to be poor.

[0091] Metal organic framework materials used in the second protective layer:

[0092] In the lithium metal reference electrode of the first aspect of the present invention, the metal organic framework material used in the process of forming the second protective layer can be prepared by a preparation method commonly used in the art.

[0093] For example, in a particularly preferred embodiment, the metal organic framework material used in the present invention is prepared from zinc nitrate and dimethyl imidazole in methanol. For example, the metal organic framework material can be obtained by dissolving zinc nitrate and dimethyl imidazole in a methanol solvent, standing at room temperature for about 12 hours, and then washing by high-speed centrifugation.

[0094] The polyvinylidene fluoride in the first protective layer:

[0095] In a preferred embodiment, the molecular weight of the polyvinylidene fluoride used in the process of forming the first protective layer is in the range of about 300,000 to about 1,100,000 Daltons, for example, about 400,000, or about 500,000, or about 600,000, or about 700,000, or about 800,000, or about 900,000, or about 1,000,000 Daltons. Here, the molecular weight of the polyvinylidene fluoride should not be too high, for example, it should not exceed about 1,100,000 Daltons, otherwise it is difficult to control the uniformity of the formed film layer, and crystallization may also occur in the formed film layer; it should not be too small, for example, it should not be less than about 300,000 Daltons, otherwise it is easy to cause the mechanical properties of the formed film to be poor.

[0096] Process parameters for forming the first protective layer:

[0097] In another preferred embodiment, in the process of forming the first protective layer, the mass ratio of the polyvinylidene fluoride and the first lithium salt used is controlled within the range of about (2.9-3.1): 1, for example, about 3.0: 1. Here, the mass ratio range should not be too large, for example, it should not exceed about 3.1: 1, otherwise the polyvinylidene fluoride and the lithium salt may not be able to effectively form an ion conductive network, affecting the formation of lithium ion channels; it should not be too small, for example, it should not be less than about 2.9: 1, otherwise it may lead to enhanced interaction between polyvinylidene fluoride, thereby hindering the migration of lithium ions.

[0098] The thickness of the first protective layer and the second protective layer:

[0099] In addition, on the one hand, in the lithium metal reference electrode of the first aspect of the present invention, the thickness of the first protective layer can be in the range of about 0.1 to about 0.5 mm, for example, about 0.2 mm, about 0.3 mm or about 0.4 mm. Here, the thickness of the first protective layer should not be too large or too small, for example, it should not exceed about 0.5 mm, otherwise it may affect the subsequent battery aluminum plastic film shell packaging; it should not be less than about 0.1 mm, otherwise it may increase the risk of damage to the protective layer during assembly, thereby insufficiently protecting the second protective layer below, and the requirements for the preparation process will also be significantly increased.

[0100] On the other hand, in the lithium metal reference electrode of the first aspect of the present invention, the thickness of the second protective layer is in the range of about 0.5 mm to about 1 mm, for example, about 0.6 mm, or about 0.7 mm, or about 0.8 mm, or about 0.9 mm. Here, the thickness of the second protective layer should not be too large or too small, for example, it should not exceed about 1 mm, otherwise it will cause the overall thickness of the reference electrode to increase, thereby affecting the thickness of the entire battery cell and affecting the subsequent packaging of the battery. It should not be less than about 0.5 mm, otherwise it may cause the mechanical properties of the second protective layer to be insufficient, and the protection effect on the reference electrode is insufficient, and the processability will be poor.

[0101] wire:

[0102] In the lithium metal reference electrode of the first aspect of the present invention, one end of the wire is electrically connected to the lithium metal component, and the other end extends out of the second protective layer and the first protective layer encapsulating the lithium metal component.

[0103] Here, the conductor may be a copper wire commonly used in the art. The copper wire may be an enameled copper wire, and the end in contact with the lithium metal component is stripped.

[0104] According to a second aspect of the present invention, the present invention provides a method for preparing a lithium metal reference electrode according to the first aspect of the present invention as described above. Here, the general features and preferred features described above for the lithium metal reference electrode in the first aspect of the present invention are also applicable to the second aspect of the present invention. The preparation method according to the second aspect of the present invention comprises the following steps 1 to 4.

[0105] Step 1:

[0106] In the preparation method of the second aspect of the present invention, step 1 includes providing the lithium metal component electrically connected to one end of the wire. The electrical connection can be achieved by commonly used means in the art, such as welding, riveting, bonding, and rolling.

[0107] Step 2:

[0108] In the preparation method of the second aspect of the present invention, step 2 includes providing a Li-IL@MOFs / polymer composite film as the second protective layer. Specifically, step 2 may include dissolving the second lithium salt in the ionic liquid to obtain an ionic liquid solution (Li-IL) of the second lithium salt, and then mixing the second lithium salt ionic liquid solution with the metal organic framework material, so that the second lithium salt ionic liquid solution is adsorbed in the metal organic framework material, and then the metal organic framework material adsorbed with the second lithium salt ionic liquid solution is uniformly mixed with the film-forming polymer and ground, and the obtained ground mixture is hot-pressed into a film to form the Li-IL@MOFs / polymer composite film, wherein the size of the Li-IL@MOFs / polymer composite film is sufficient to encapsulate the lithium metal component.

[0109] In a preferred embodiment, the adsorption process in the above step 2 includes maintaining the mixture containing the second lithium salt ionic liquid solution and the metal organic framework material at a temperature of about 100 to about 120°C (e.g., about 110°C) and a vacuum degree of about -0.06MPa to about -0.08MPa (e.g., about -0.07MPa) for about 12 to about 24 hours (e.g., about 18 hours) to allow the second lithium salt ionic liquid solution to be adsorbed in the metal organic framework material. Here, the temperature of the adsorption process should not be too high or too low, for example, it should not exceed about 120°C, otherwise it is easy to cause the structure of the metal organic framework material to be damaged, and the risk of structural collapse will increase; it should not be lower than about 100°C, otherwise it will be unfavorable for the adsorption of the lithium salt ionic liquid solution. In addition, the vacuum degree of the adsorption process should not be too high or too low, for example, it should not exceed about -0.08MPa, otherwise it will have higher requirements on the vacuum equipment and increase the cost; it should not be lower than about -0.06MPa, otherwise the adsorbed water, organic solvent and other molecules cannot be completely removed, and the lithium salt ionic liquid solution will be incompletely adsorbed. In addition, the adsorption process should not be too long or too short, for example, it should not exceed about 24 hours, otherwise it will increase the preparation cycle time and affect the preparation efficiency, and it should not be shorter than about 12 hours, otherwise the lithium salt ionic liquid solution will not be fully adsorbed.

[0110] In another preferred embodiment, the hot pressing film forming in step 2 includes film forming for about 2 to about 5 minutes (for example, about 3 minutes or about 4 minutes) at a temperature of about 70 to about 80°C (for example, about 75°C) and a pressure of about 18 to about 30MPa (for example, about 21MPa, about 24MPa or about 27MPa). Here, the temperature of the hot pressing film forming should not be too high or too low, for example, it should not exceed about 80°C, otherwise the uniformity of the film formation is easily affected; it should not be lower than about 70°C, otherwise the polymer molecules that play a cross-linking role may not reach the glass transition temperature and film formation cannot be achieved. In addition, the pressure of the hot pressing film forming should not be too high or too low, for example, it should not exceed about 30MPa, otherwise it may be difficult to control the thickness of the film, and it may exceed the pressure bearing capacity of the mold and affect the mold; it should not be lower than about 18MPa, otherwise the film thickness may be too large and the target film thickness cannot be achieved. In addition, the hot pressing film forming time should not be too long or too short, for example, it should not exceed about 5 minutes, otherwise it may cause film shrinkage and affect the uniformity of film forming; it should not be shorter than about 2 minutes, otherwise it may cause more pores and defects inside the material.

[0111] Step 3:

[0112] In the preparation method of the second aspect of the present invention, step 3 includes providing a polymer solid electrolyte membrane of the first protective layer. Specifically, step 3 may include dissolving the polyvinylidene fluoride and the first lithium salt in a volatile organic solvent to form a solution, and volatilizing the organic solvent in the solution to form the polymer solid electrolyte membrane, wherein the size of the polymer solid electrolyte membrane is sufficient to encapsulate the lithium metal component encapsulated by the Li-IL@MOFs / polymer composite membrane.

[0113] The volatile organic solvent used in the above step 3 is not particularly limited, as long as it can effectively dissolve the polyvinylidene fluoride and the first lithium salt and is easily volatilized in the subsequent film forming process. For example, in a preferred embodiment, the volatile organic solvent that can be used includes one or more of acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.

[0114] In another preferred embodiment, the solid content of the solution formed in the above step 3 can be controlled within a range of about 5 to about 10 weight %, for example, about 6 weight %, about 7 weight %, about 8 weight % or about 9 weight %. Here, the solid content should not be too large or too small, for example, it should not exceed about 10 weight %, otherwise the film formation uniformity may be affected and the film formation may be uneven; it should not be less than about 5 weight %, otherwise bubbles may be easily generated during the solvent volatilization process, and the film formation uniformity may also be easily affected.

[0115] In another preferred embodiment, the process of forming the polymer solid electrolyte membrane in the above step 3 includes forming the film at a temperature of about 40 to about 60°C and a vacuum degree of about -0.04 to about -0.08MPa. Here, the temperature of the film forming process should not be too high or too low, for example, it should not exceed about 60°C, otherwise the solvent may evaporate rapidly and easily lead to uneven film formation; it should not be lower than about 40°C, otherwise the solvent may not evaporate completely. In addition, the vacuum degree of the film forming process should not be too high or too low, for example, it should not exceed about -0.08MPa, otherwise it may cause many bubbles to be generated inside the membrane; it should not be lower than about -0.04MPa, otherwise it may cause incomplete solvent removal.

[0116] Step 4:

[0117] In the preparation method of the second aspect of the present invention, step 4 includes encapsulating the lithium metal component obtained in step 1 with the Li-IL@MOFs / polymer composite membrane obtained in step 2 and the polymer solid electrolyte membrane obtained in step 3 in sequence to form the lithium metal reference electrode. The lithium metal reference electrode obtained after encapsulation comprises the polymer solid electrolyte membrane, the Li-IL@MOFs / polymer composite membrane and the lithium metal component in order from the outside to the inside, wherein the other end of the wire electrically connected to the lithium metal component extends out of the polymer solid electrolyte membrane and the Li-IL@MOFs / polymer composite membrane encapsulating the lithium metal component.

[0118] In a preferred embodiment, step 4 may include stacking the Li-IL@MOFs / polymer composite membrane obtained from step 2 and the lithium metal reference electrode current collector obtained from step 1 on the polymer solid electrolyte membrane obtained from step 3 in the order of "Li-IL@MOFs / polymer composite membrane", "lithium metal component" and "Li-IL@MOFs / polymer composite membrane", and then further providing the polymer solid electrolyte membrane of the first protective layer on the uppermost Li-IL@MOFs / polymer composite membrane to form a combination; and then fusing and compounding the polymer solid electrolyte membrane and the Li-IL@MOFs / polymer composite membrane located in the encapsulation area in the obtained combination to complete the encapsulation.

[0119] Alternatively, step 4 may include stacking the polymer solid electrolyte membrane obtained from step 3, the Li-IL@MOFs / polymer composite membrane obtained from step 2, and the lithium metal component body obtained from step 1 in the order of "polymer solid electrolyte membrane", "Li-IL@MOFs / polymer composite membrane", "lithium metal component", "Li-IL@MOFs / polymer composite membrane" and "polymer solid electrolyte membrane" to form a combination; and then fusing and compounding the polymer solid electrolyte membrane and the Li-IL@MOFs / polymer composite membrane located in the encapsulation area of ​​the obtained combination to complete the encapsulation.

[0120] Here, the meaning of the packaging area is as shown in the attached manual. Figure 3 As shown in FIG. 1 , in the formed assembly, the polymer solid electrolyte membrane encapsulating the lithium metal component and the region of the Li-IL@MOFs / polymer composite membrane that does not overlap with the lithium metal component.

[0121] In addition, the fusion compound described above preferably includes hot pressing for about 15 to about 30 seconds (for example, about 20 seconds or about 25 seconds) at a temperature of about 40 to about 70°C (for example, about 50°C or about 60°C) and a pressure of about 5 to about 10Mpa (for example, about 6MPa, about 7MPa, about 8MPa or about 9MPa). Here, the temperature of the fusion compound should not be too high or too low, for example, it should not exceed about 70°C, otherwise it is easy to cause film shrinkage, resulting in loose packaging; it should not be lower than about 40°C, otherwise it may cause the films of the first protective layer and the second protective layer to fail to soften and thus achieve effective fusion, which may also affect the sealing of the package. In addition, the pressure of the fusion compound should not be too high or too low, for example, it should not exceed about 10MPa, otherwise it may cause the thickness of the packaging area to become smaller and increase the risk of breakage; it should not be lower than about 5MPa, otherwise it may cause the first protective layer and the second protective layer to fail to be effectively packaged and fused. In addition, the fusion and compounding time should not be too long or too short, for example, it should not exceed about 30 seconds, otherwise the thickness of the packaging area may become smaller, and it should not be shorter than about 15 seconds, otherwise the packaging area may not be sealed tightly.

[0122] According to the third aspect of the present invention, the present invention provides a three-electrode lithium-ion battery, wherein the three-electrode lithium-ion battery comprises a lithium metal reference electrode according to the first aspect of the present invention or a lithium metal reference electrode prepared according to the preparation method described in the second aspect. Here, the general features and preferred features described above about the lithium metal reference electrode in the first and second aspects of the present invention are also applicable to the third aspect of the present invention.

[0123] In the three-electrode lithium-ion battery described in the third aspect of the present invention, the three-electrode lithium-ion battery comprises a battery cell, wherein the battery cell comprises a separator, a negative electrode and a positive electrode.

[0124] In a preferred embodiment, the battery comprises a cell and a reference electrode, wherein the cell comprises a separator, a negative electrode, a separator, a positive electrode, a separator, a negative electrode and a separator arranged alternately in the following order, and the reference electrode is placed outside the cell near the negative electrode, thereby forming a three-electrode battery system. The reference electrode does not need an external separator because it contains a double-layer interface protection layer.

[0125] In a particularly preferred embodiment, the dimensions of the lithium metal reference electrode are smaller than the dimensions of the negative electrode.

[0126] The present invention is further described in detail below with reference to specific embodiments.

[0127] Examples 1 to 3: General method for preparing a three-electrode lithium-ion battery:

[0128] The materials used in this method are shown in Table 1.

[0129] Combined with Figures 1 to 5 :

[0130] (1) A lithium metal component 3 having the specifications shown in Table 1 is provided, and the lithium metal component 3 is electrically connected to one end of a copper wire as a conductor 4 by rolling.

[0131] (2) Providing a Li-IL@MOFs / polymer composite membrane as a second protective layer 2:

[0132] Specifically, the second lithium salt is dissolved in an ionic liquid to obtain an ionic liquid solution of the second lithium salt, and the metal organic framework material and the ionic liquid solution of the second lithium salt are mixed in a weight ratio of about 1.5:1 at a temperature of about 110° C. and a vacuum degree of -0.07 MPa for about 18 hours, so that the second lithium salt ionic liquid solution is fully adsorbed in the metal organic framework material, wherein the metal organic framework material is obtained by mixing zinc nitrate and dimethylimidazole in methanol, standing at room temperature for about 12 hours, and then washing by high-speed centrifugation.

[0133] The metal organic framework material adsorbed with the second lithium salt ionic liquid solution is then uniformly mixed and ground with polyvinyl alcohol having an average molecular weight of about 130,000 Daltons as a film-forming polymer, and the ground mixture obtained is hot-pressed into a film at a temperature of about 75° C. and a certain pressure to form the Li-IL@MOFs / polymer composite membrane, wherein the size of the Li-IL@MOFs / polymer composite membrane is sufficient to encapsulate the lithium metal component.

[0134] (3) A polymer solid electrolyte membrane is provided as the first protective layer 1 .

[0135] Specifically, polyvinylidene fluoride having an average molecular weight of about 400,000 Daltons and the first lithium salt are dissolved in a volatile organic solvent in a mass ratio of about 3:1 to form a solution, and the organic solvent in the solution is volatilized to form the polymer solid electrolyte membrane, wherein the size of the polymer solid electrolyte membrane is sufficient to encapsulate the lithium metal component encapsulated by the Li-IL@MOFs / polymer composite membrane;

[0136] (4) The lithium metal component obtained in the above step (1) is encapsulated with the Li-IL@MOFs / polymer composite membrane obtained in the above step (2) and the polymer solid electrolyte membrane obtained in the above step (3) in sequence to form the lithium metal reference electrode 12, wherein the encapsulation is completed by hot pressing the Li-IL@MOFs / polymer composite membrane and the polymer solid electrolyte membrane located in the encapsulation area at a temperature of about 55° C. and a pressure of about 7.5 MPa for 25 seconds. The obtained lithium metal reference electrode comprises the polymer solid electrolyte membrane, the Li-IL@MOFs / polymer composite membrane and the lithium metal component in order from the outside to the inside, wherein the other end of the wire electrically connected to the lithium metal component extends out of the polymer solid electrolyte membrane and the Li-IL@MOFs / polymer composite membrane encapsulating the lithium metal component.

[0137] (5) Providing a battery cell comprising a separator 5, a negative electrode 6 and a positive electrode 7, wherein the battery cell comprises a separator 5, a negative electrode 6, a separator 5, a positive electrode 7, a separator 5, a negative electrode 6 and a separator 5 arranged alternately in the following order. The battery cell is combined with a lithium metal reference electrode prepared as above to form a three-electrode lithium-ion battery, wherein the lithium metal reference electrode is placed outside the battery cell and close to the negative electrode, and the size of the lithium metal reference electrode is smaller than the size of the negative electrode (about 54 cm 2 ).

[0138] The negative electrode 6 and the negative electrode tab 9, the positive electrode 7 and the positive electrode tab 8 are connected by ultrasonic welding, and the negative electrode tab 9 and the positive electrode tab 8 are fused and bonded with the aluminum-plastic film by the tab glue 10 through top-side heat sealing.

[0139] The reference electrode 12 is connected to the reference electrode tab 11 through a copper wire, and the copper wire is welded on the reference electrode tab 11 to form a conductive path from the lithium metal component 3 to the reference electrode tab 11 .

[0140] Some of the preparation process conditions used in the above examples are summarized in Table 1 below:

[0141] Table 1:

[0142]

[0143] The three-electrode lithium-ion batteries prepared in Examples 1 to 3 were charged in stages. To avoid polarization during high-rate (high-current) direct charging that causes lithium deposition on the negative electrode surface, the battery was charged using a multi-stage constant current (CC) charging method to ensure that the negative electrode potential was within a safe range while reducing the risk of polarization during the charging process and lithium deposition on the negative electrode surface, thereby reducing damage to the battery and extending the battery life. The negative electrode potential during the charging process was monitored using a loop formed between the reference electrode and the negative electrode.

[0144] For example, the step-by-step charging verification (multi-stage constant current charging) process of the three-electrode lithium-ion battery of Example 3 is as follows: Figure 6 shown.

[0145] Figure 6 The negative electrode-reference potential value in the graph is actually the lithium potential (vs.Li / Li + ), see Table 2 below for specific values. When the potential value is less than or equal to 0V (vs.Li / Li + ) has the risk of lithium deposition, greater than 0V (vs.Li / Li + ) when the lithium ion battery is less than 100 MW, there is no risk of lithium deposition.

[0146] Table 2 shows the negative electrode-reference potential monitoring results of the three-electrode lithium-ion battery prepared in Example 3 at different charging cumulative SOCs (battery states of charge).

[0147] Table 2:

[0148] Charging SOC (%) Accumulated charging SOC (%) Negative electrode-reference potential (mV) 10 10 179.0 30 40 16.0 10 50 13.0 15 65 12.5 15 80 12.5 10 90 21.0 8 98 29.0

[0149] Depend on Figure 6 It can be seen from the results in Table 2 above that the three-electrode battery of the present invention can accurately verify the step charging mode (multi-stage constant current charging) during charging without affecting the lithium battery, and can easily determine whether there is a risk of lithium plating at the negative electrode, and provide a reference for the subsequent optimization of the charging method.

[0150] The stability test of the three-electrode lithium-ion battery prepared in Examples 1 to 3 includes connecting the positive electrode of the electrochemical test device to the negative electrode tab 9, and connecting the negative electrode to the reference electrode tab 11, and testing the stability of the negative electrode-reference electrode within a voltage protection range of about -0.5V to 3V, wherein the battery state of charge SOC is controlled to a value between about 10% and about 25%. For example, the stability test results of the three-electrode lithium-ion battery prepared in Example 3 are as follows: Figure 7As shown, due to the self-discharge characteristics of lithium-ion batteries, the voltage fluctuation range is maintained within about 1 to 3 mV during the test time of about 400 hours. The self-discharge of lithium-ion batteries is an inherent characteristic of lithium-ion batteries. It is affected by the formation and decomposition of the solid electrolyte interface (SEI film), temperature and other factors. During the long-term test, the potential of the negative electrode-reference electrode will rise to a certain extent. In this embodiment, the potential change of the negative electrode-reference electrode in the 400-hour test is about 3 mV, which also reflects the low self-discharge rate of the battery from the side.

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions claimed to be protected by the present invention.

Claims

1. A lithium metal reference electrode for a three-electrode lithium-ion battery, characterized in that The lithium metal reference electrode comprises: a lithium metal component, a wire, a first protective layer and a second protective layer, wherein The lithium metal component contains ≥98.0 wt %, preferably ≥99.0 wt %, more preferably ≥99.9 wt % of lithium; The second protective layer comprises a Li-IL@MOFs / polymer composite film formed by a metal organic framework material adsorbed with a second lithium salt ionic liquid solution and a film-forming polymer, and the film encapsulates the lithium metal component; The first protective layer comprises a polymer solid electrolyte membrane formed of polyvinylidene fluoride and a first lithium salt, the membrane encapsulating the lithium metal component and the second protective layer; and One end of the wire is electrically connected to the lithium metal component, and the other end of the wire extends out of the second protective layer and the first protective layer encapsulating the lithium metal component.

2. The lithium metal reference electrode according to claim 1, characterized in that The lithium metal component is selected from lithium foil, lithium sheet, lithium plate or lithium mesh, and its thickness is preferably in the range of 0.1 to 1 mm; and / or The conductive wire comprises copper wire; and / or The thickness of the first protective layer is in the range of 0.1 to 0.5 mm; and / or The thickness of the second protective layer is in the range of 0.5 mm to 1 mm.

3. The lithium metal reference electrode according to claim 1, characterized in that The first lithium salt and the second lithium salt each independently comprise one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide) and lithium bis(trifluoromethylsulfonylimide), Preferably, the first lithium salt and the second lithium salt are the same and are selected from lithium hexafluorophosphate, lithium bis(difluorosulfonyl imide) or lithium bis(trifluoromethylsulfonyl imide).

4. The lithium metal reference electrode according to any one of claims 1 to 3, characterized in that The polyvinylidene fluoride has a molecular weight in the range of 300,000 to 1,100,000 Daltons; and / or The mass ratio of the polyvinylidene fluoride to the first lithium salt is in the range of (2.9-3.1):1; and / or The ionic liquid comprises one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide; and / or The film-forming polymer comprises polyvinyl alcohol having a molecular weight in the range of 120,000 to 150,000 Daltons; and / or The metal organic framework material is prepared from zinc nitrate and dimethylimidazole in methanol.

5. The lithium metal reference electrode according to any one of claims 1 to 3, characterized in that During the formation of the second protective layer of Li-IL@MOFs / polymer composite film, The molar concentration of the second lithium salt ionic liquid solution used is in the range of 1 to 3 mol / L; and / or The mass ratio of the metal organic framework material to the second lithium salt ionic liquid solution is in the range of (1.4-1.6):1; and / or The mass ratio of the metal organic framework material adsorbed with the second lithium salt ionic liquid solution to the film-forming polymer is in the range of (2-2.5):

1.

6. A method for preparing a lithium metal reference electrode according to any one of claims 1 to 5, characterized in that The method comprises the following steps: Step 1: providing the lithium metal component electrically connected to one end of the wire; Step 2: providing a Li-IL@MOFs / polymer composite membrane as the second protective layer, comprising dissolving the second lithium salt in the ionic liquid to obtain the second lithium salt ionic liquid solution, mixing the second lithium salt ionic liquid solution with the metal organic framework material, so that the second lithium salt ionic liquid solution is adsorbed in the metal organic framework material, and then uniformly mixing and grinding the metal organic framework material adsorbed with the second lithium salt ionic liquid solution and the film-forming polymer, and hot-pressing the obtained ground mixture into a film to form the Li-IL@MOFs / polymer composite membrane, wherein the size of the Li-IL@MOFs / polymer composite membrane is sufficient to encapsulate the lithium metal component; Step 3: providing a polymer solid electrolyte membrane as the first protective layer, comprising dissolving the polyvinylidene fluoride and the first lithium salt in a volatile organic solvent to form a solution, and volatilizing the organic solvent in the solution to form the polymer solid electrolyte membrane, wherein the size of the polymer solid electrolyte membrane is sufficient to encapsulate the lithium metal component encapsulated by the Li-IL@MOFs / polymer composite membrane; Step 4: The lithium metal component obtained in step 1 is encapsulated in sequence with the Li-IL@MOFs / polymer composite membrane obtained in step 2 and the polymer solid electrolyte membrane obtained in step 3 to form the lithium metal reference electrode, which comprises the polymer solid electrolyte membrane, the Li-IL@MOFs / polymer composite membrane and the lithium metal component in order from the outside to the inside, wherein the other end of the wire electrically connected to the lithium metal component extends out of the polymer solid electrolyte membrane and the Li-IL@MOFs / polymer composite membrane encapsulating the lithium metal component.

7. The preparation method according to claim 6, characterized in that: The step 4 comprises: The Li-IL@MOFs / polymer composite membrane obtained in step 2 and the lithium metal component obtained in step 1 are stacked in the order of "Li-IL@MOFs / polymer composite membrane", "lithium metal component" and "Li-IL@MOFs / polymer composite membrane" on the polymer solid electrolyte membrane obtained in step 3, and then a polymer solid electrolyte membrane as the first protective layer is further provided on the uppermost Li-IL@MOFs / polymer composite membrane to form a composite body; or The polymer solid electrolyte membrane obtained in step 3, the Li-IL@MOFs / polymer composite membrane obtained in step 2, and the lithium metal component body obtained in step 1 are stacked in the order of "polymer solid electrolyte membrane", "Li-IL@MOFs / polymer composite membrane", "lithium metal component", "Li-IL@MOFs / polymer composite membrane" and "polymer solid electrolyte membrane" to form a composite body; and The polymer solid electrolyte membrane and the Li-IL@MOFs / polymer in the obtained assembly located in the encapsulation area are then fused and composited to complete the encapsulation, wherein the fusion composite preferably includes hot pressing at a temperature of 40 to 70° C. and a pressure of 5 to 10 MPa for 15 to 30 seconds.

8. The preparation method according to claim 7, characterized in that: The adsorption process in step 2 comprises maintaining the mixture comprising the second lithium salt ionic liquid solution and the metal organic framework material at a temperature of 100 to 120° C. and a vacuum degree of −0.06 MPa to −0.08 MPa for 12 to 24 hours to allow the second lithium salt ionic liquid solution to be adsorbed in the metal organic framework material; and / or The hot-pressing film forming in the step 2 includes maintaining at a temperature of 70 to 80° C. and a pressure of 18 to 30 MPa for 2 to 5 minutes.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The volatile organic solvent used in step 3 comprises one or more of acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone; and / or The forming of the polymer solid electrolyte membrane in step 3 includes forming the membrane at a temperature of 40 to 60° C. and a vacuum degree of −0.04 to −0.08 MPa; and / or The solid content of the solution formed in step 3 is controlled within a range of 5 to 10 wt %.

10. A three-electrode lithium-ion battery comprising a battery cell, wherein the battery cell comprises a separator, a negative electrode and a positive electrode, characterized in that: The three-electrode lithium-ion battery also includes a lithium metal reference electrode according to any one of claims 1 to 5 or a lithium metal reference electrode prepared by the preparation method according to any one of claims 6 to 9, wherein the lithium metal reference electrode is preferably placed outside the battery cell and closer to the negative electrode relative to the positive electrode, and the size of the lithium metal reference electrode is preferably smaller than that of the negative electrode.

Citation Information

Patent Citations

  • A soft-pack battery with a constant potential reference electrode and a preparation method thereof

    CN114284564B

  • Manufacturing method of reference electrode and reference electrode

    CN117007658A

  • Preparation method of composite solid electrolyte based on metal organic framework / ionic liquid

    CN111180791A

  • Packaging method of metal lithium reference electrode for lithium battery

    CN112054162A

  • Preparation method of lithium metal reference electrode and lithium metal reference electrode

    CN112563459A

Cited By

  • Three-electrode button cell

    CN224096691U